2015
DOI: 10.2147/ccid.s74401
|View full text |Cite
|
Sign up to set email alerts
|

Facial skin pores: a multiethnic study

Abstract: Skin pores (SP), as they are called by laymen, are common and benign features mostly located on the face (nose, cheeks, etc) that generate many aesthetic concerns or complaints. Despite the prevalence of skin pores, related literature is scarce. With the aim of describing the prevalence of skin pores and anatomic features among ethnic groups, a dermatoscopic instrument, using polarized lighting, coupled to a digital camera recorded the major features of skin pores (size, density, coverage) on the cheeks of 2,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
80
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 18 publications
11
80
1
Order By: Relevance
“…An additional benefit of the developed method was the small number of steps required for the production of the mimics, which resulted in reduced cost, time and experimental errors. Interferometry measurements further provided information on the mimics’ roughness (figure 1 c , d ) with the skin mimic exhibiting a roughness of 15.48 ± 0.33 µm, comparable to the average values of 10–30 µm reported in the literature [16,17,36,39].
Figure 1.A large area ( a ) and a zoomed-in ( b ) SEM micrograph of the PU4 biomimic showing the high-fidelity replication of the human skin with 3D topography and pore diameters.
…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…An additional benefit of the developed method was the small number of steps required for the production of the mimics, which resulted in reduced cost, time and experimental errors. Interferometry measurements further provided information on the mimics’ roughness (figure 1 c , d ) with the skin mimic exhibiting a roughness of 15.48 ± 0.33 µm, comparable to the average values of 10–30 µm reported in the literature [16,17,36,39].
Figure 1.A large area ( a ) and a zoomed-in ( b ) SEM micrograph of the PU4 biomimic showing the high-fidelity replication of the human skin with 3D topography and pore diameters.
…”
Section: Resultssupporting
confidence: 80%
“…The mean diameter of the pores i.e. of the openings of the stratum corneum connected to the sweat glands, can vary depending on various parameters such as age, ethnicity, sex and skin pore characteristics, typically exhibiting a range of diameters from 60 to 80 µm and a distribution of 200 pores cm −2 [36–38]. The SEM images (figure 1 a , b ) demonstrate high-replication accuracy of the fabricated skin mimics exhibiting three-dimensional topography and pore distribution, closely similar to human skin, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed Demodex mites more frequently in Black subjects, which may be related to the increased sebum secretion, altered sebum content and increased pore size in this ethnic group [33]. However, conflicting data regarding the association of pore size with sebum secretion and other factors such as age, gender, and sun exposure are reported in the literature [34]. Regarding our results, a possible modifying effect of a new climate (the study was performed in Munich, Germany) on the pore size of Asian and Black subjects remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a study conducted by Flament et al [23] with a larger sample of subjects (n = 2585 women) found individual pore surface on cheeks in the range of 0.06 to 0.16 mm 2 , which means on average 0.37 mm of diameter (i.e. 370 µm).…”
Section: Pore Size Evaluationmentioning
confidence: 98%